Master and commander [videorecording (Blu-Ray)] : the far side of the world - Weir, Peter, 1944-; Collee, John; Crowe, Russell, 1964-; Bettany, Paul, 1971-; D'Arcy, James, 1975-; Woodall, Edward, 1967-; Larkin, Chris, 1967-; Pirkis, Max; Randall, Jack, 1988-; Boyd, Russell, 1944-; Smith, Lee; Davies, Iva; et al. (20th Century Fox Home Entertainment, 2007)
The year is 1805 and Europe has fallen to Napoleon. The Royal Navy is the only thing standing in his way to total victory. Off the coast of South America, a new conflict is brewing. Captain Jack 'Lucky Jack' Aubrey and his Man-of-War HMS Surprise is under orders to sink or capture the French privateer Acheron, which has been deployed to the region. After seven weeks of uneventful sailing, the Acheron strikes first, all but crippling the Surprise in an engagement in which Aubrey realizes his enemy's ship is nautically superior to his own. Along with his close friend and confidant, ship's surgeon Stephan Maturin, Aubrey is now faced with the choice of retreating to England and admitting defeat or remaining at the Acheron's mercy. Aubrey must now do the impossible if he is to survive, repair his ship, catch up to his enemy and defeat the Acheron.